A cross-sectional study on colorectal cancer screening knowledge and barriers among university students - Hebatalla Abdelmaksoud Abdelmonsef Ahmed; Bander Saad Albagawi; Amany Hamed AboZayed; Ahmed Yousef; Marzouk M. Marzouk; Ibrahim Naif Alenezi; Abeer A. Almowafy; Hoda Ali Ahmed Shiba (BMC Public Health)
Abstract Background Colorectal cancer (CRC) is a significant contributor to cancer-related mortality on a global scale. Timely identification by screening can decrease the morbidity and mortality associated with CRC. This study aimed to evaluate the level of knowledge and perceived barriers related to CRC screening among university students. Methods A cross-sectional study was carried out among university students between October 2022 and July 2023. Data were gathered using an online survey that evaluated knowledge of CRC, with a specific emphasis on sociodemographic information, risk factors for CRC, warning signs and symptoms, and the available screening methods. Results Out of the 2090 students, 74.8% were female, 54.3% were enrolled in the Faculty of Human Medicine, and 20.4% had a family history of CRC. The general knowledge of CRC and its risk factors was inadequate, as indicated by mean scores of 15.95 ± 6.5 and 3.9 ± 1.95, respectively. A total of 5.3% of the participants had received CRC screening, with colonoscopy being the most frequently employed screening method. In their perspective, the primary obstacles to CRC screening were the absence of endorsement from healthcare professionals, feelings of embarrassment, and apprehension over the outcomes. Conclusion The study highlights the need for targeted educational campaigns and interventions to improve CRC awareness among university students and address identified obstacles toward screening. However, findings are limited by self-reported data, which may introduce recall bias and affect generalizability.